(untitled) (Scientific journal of the Fergana State University, 2023)
Gossipol and gossypoloid substances, which are a polyphunctional compound, have a high biological activity. The pharmacological properties of metallocomplexes obtained by the Schiff basis of gossipol have been determined a number of higher than that of their Schiff bases. On theSchiff basis of gossypol, by immobilizing the fiber sorbents, the optimal conditions of some heavy metals were studied.